2010
DOI: 10.1152/ajprenal.00309.2009
|View full text |Cite
|
Sign up to set email alerts
|

Voiding function in obese and type 2 diabetic female rats

Abstract: The effects of obesity and type 2 diabetes (DMII) on the lower urinary tract (LUT) were characterized by evaluating voiding function and anatomy in female Zucker diabetic fatty (ZDF) rats. Age-matched female virgin rats were separated into three experimental groups: Zucker lean rats (control; normal diet, n = 22), ZDF rats (obese+nondiabetic; low-fat diet, n = 22), and ZDF rats (obese+diabetic; high-fat diet, n = 20). Rats were placed on their specified diet for 10 wk before urodynamic LUT evaluation. A suprap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 32 publications
1
36
0
Order By: Relevance
“…These findings are suggestive of an inflammatory process in the stroma of the bladder in the diabetic state may be related to oxidative stress associated with characteristics complications of diabetes mellitus. The severity of bladder injuries is also correlated to the duration of diabetes as observed in other studies 12,20 . Most studies, however, have not correlated morphological bladder lesions with the duration of diabetes mellitus and urodynamic evaluation.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…These findings are suggestive of an inflammatory process in the stroma of the bladder in the diabetic state may be related to oxidative stress associated with characteristics complications of diabetes mellitus. The severity of bladder injuries is also correlated to the duration of diabetes as observed in other studies 12,20 . Most studies, however, have not correlated morphological bladder lesions with the duration of diabetes mellitus and urodynamic evaluation.…”
Section: Discussionsupporting
confidence: 68%
“…Gasbarro et al 20 carried out histological analysis of the urethra in rats after six weeks of induction of diabetes and found that the external sphincter showed edema and fibrosis periurethral muscle layer. This infiltration of collagen leads to a sharp discontinuity of the urethral striated muscle structure compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…This is primarily due to the relative ease of inducing type I diabetes in animal models, typically using either alloxan or high doses of STZ, and the lower costs associated with developing and maintaining animals with type I diabetes. Unfortunately, the literature on the effects of type II diabetes on bladder function is sparse (21). Studies determining the time course of diabetic bladder dysfunction in type II diabetic animal models are severely lacking along with studies determining whether bladder dysfunction is similar in type I vs. type II diabetic animal models (13).…”
mentioning
confidence: 99%
“…Alterations in both urodynamic profile and bladder reactivity in vitro have been described in different animal models of obesity (Rahman et al, 2007;Gasbarro et al, 2010;Lee et al, 2011;Leiria et al, 2012). However, no study has evaluated the potential implications of impairment of USM relaxations contributing to overall obesity-related micturition problems.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of OAB and metabolic syndrome in the U.S. adult population is 16% and 26%, respectively (Irwin et al, 2011). Animal models have provided evidence to confirm a relationship between metabolic syndrome/hyperlipidemia and OAB symptoms (Rahman et al, 2007;Nobe et al, 2008;Lee et al, 2011;Gasbarro et al, 2010). Obesity-associated insulin resistance has been shown to play an important role in OAB pathophysiology in mice (Leiria et al, 2012).…”
Section: Introductionmentioning
confidence: 99%